0765 Reliability And Validity Study Of The Chinese Version Of Narcolepsy Severity Scale For Adult Patients With Narcolepsy Type 1. (27th May 2020) - Li, C; Zhang, C; Han, F
Abstract: Introduction: Narcolepsy is a chronic sleep disorder that can affects significantly patient functioning, involving social, work, and affective life. At present, many drugs have been developed to treat narcolepsy efficiently. But there is no Chinese version of Narcolepsy Severity Scale (NSS) available yet, for that the aim of this study is to translate the NSS into Chinese and evaluate reliability and validity of the NSS in adult patients with narcolepsy type 1 (NT1). Methods: NSS was translated according to the standard procedures of double-back translation and cross-cultural adaptation steps. The NSS was administered to 62 adult patients (42 males, 20 females; mean age 34 years; range 19 to 67 years) with NT1 from April 2019 to December 2019. The validity of the scale was assessed by the exploratory factor analysis, discriminant validity and convergent validity. The reliability was assessed by the Cronbach's α coefficient and test-retest reliability. Results: Three common factors were extracted and 15 items explained 57.4% of the total variance. Cronbach's α coefficient for total scale was 0.767 and Cronbach's α for three dimensions ranged from 0.729 to 0.787. Scores were significant difference between treated and untreated group in dependent samples (p=0.036), but no differences in the independent samples (p>0.05). The NSS had good correlations with Epworth Sleepiness Scale (r=0.302, p=0.017) and Insomnia Severity Index (r=0.526, p=0.000). The NSS showed good test-retest reliability (r=0.72, p=0.029). Conclusion: The Chinese version of NSS was proved to be valid and reliable and can be used to evaluate the severity and consequences of symptoms in Chinese adult patients with NT1. Support: